2017
DOI: 10.1002/ijc.30911
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic screening for synchronous esophageal neoplasia among patients with incident head and neck cancer: Prevalence, risk factors, and outcomes

Abstract: Esophageal squamous-cell neoplasia (ESCN) is a common second primary neoplasia found in patients with head-and-neck squamous-cell carcinoma (HNSCC). This study sought to identify the risk factors for synchronous ESCN and how they influence survival in HNSCC patient. Eight hundred and fifteen incident HNSCC patients were prospectively recruited for endoscopy screening for ESCN using white-light imaging, narrow-band imaging, Lugol chromoendoscopy, and pathological confirmation. Associated lifestyle and clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 31 publications
(102 reference statements)
6
70
3
Order By: Relevance
“…To our knowledge, there was no study reported the positive association of facial flushing with reflux esophagitis and Barrett's esophagus (Table ). Although previous studies have reported ALDH2 deficiency increased the risk of esophageal cancer, we did not find the similar significant result in ESCC risk, possibly due to small sample size (n = 44). A future study needs to examine the mechanisms of the relationship between alcohol metabolizing‐related genes and the risks of reflux esophagitis and Barrett's esophagus (Table ).…”
Section: Discussioncontrasting
confidence: 98%
“…To our knowledge, there was no study reported the positive association of facial flushing with reflux esophagitis and Barrett's esophagus (Table ). Although previous studies have reported ALDH2 deficiency increased the risk of esophageal cancer, we did not find the similar significant result in ESCC risk, possibly due to small sample size (n = 44). A future study needs to examine the mechanisms of the relationship between alcohol metabolizing‐related genes and the risks of reflux esophagitis and Barrett's esophagus (Table ).…”
Section: Discussioncontrasting
confidence: 98%
“…The American Society of Clinical Oncology recommends symptom oriented esophageal screening in HNC survivors 18 . Nevertheless, the incidence of www.nature.com/scientificreports www.nature.com/scientificreports/ synchronous esophageal cancer might differ between eastern and western countries 5,13,19,20 . Compared with Western countries, studies from Eastern Asia have demonstrated a higher incidence of synchronous EC.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol drinking, tobacco smoking and betel nut chewing, as well as the ALDH-2 polymorphism might explain these geographic differences 21,22 . Furthermore, increased awareness of the risk of synchronous EC in patients with HNC may change a physicians' and local hospital's treatment guidelines, by using routine endoscopic screening instead of symptom oriented evaluation 10,11,14,20 . Alcohol drinking and tumor location over the oropharynx and hypopharynx, were previously identified by the authors as risk factors for developing synchronous EC.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal squamous-cell carcinoma (ESCC) is one of the most common second primary cancers occurring in patients with head and neck squamous-cell carcinoma (HNSCC) [1]. Development of second ESCC significantly compromises HNSCC patients’ survival [2,3]. Habitual alcohol, betel nut, and cigarette use are established risk factors for ESCC [4], but the influence of these carcinogens on the development of second ESCC in HNSCC patients is less clear.…”
Section: Introductionmentioning
confidence: 99%